PHENOTYPE FREQUENCIES OF RH AND KELL BLOOD GROUPSYSTEMS IN BLOOD TRANSFUSION DEPARTMENT OFAVICENNA MILITARY HOSPITAL, MARRAKECH, MOROCCO (International Journal of Medicine & Health Research (IJMHR) (ISSN 2395-3586), 2024)
The purpose of our study is presenting new national statistics of phenotypic prevalence Rhesus systems (Rh) and Kell usinga new sample of blood donors.